Efficacy and Safety of Traditional Chinese Medicine Based on the Method of "Nourishing Kidney and Clearing Heat" as Adjuvant in the Treatment of Diabetes Mellitus Patients with Periodontitis: A Systematic Review and Meta-Analysis. (27th August 2022) - Jin, Wenqin; Li, Lingfeng; Ai, Huangping; Jin, Zhao; Zuo, Yuling
Abstract : Objective . The aim of this systematic review and meta-analysis was to assess the efficacy and safety of traditional Chinese medicine based on the method of "nourishing kidney and clearing heat" as an adjuvant in the treatment of diabetes mellitus patients with periodontitis. Methods . An electronic literature search was conducted in the China National Knowledge Infrastructure (CNKI), Wanfang Data, Chinese Scientific Journals Database (VIP), Chinese Biomedical Literature Database (CBM), PubMed, EMBASE, Web of Science, and Cochrane Library databases for articles published until October 2021. The primary outcomes were probing pocket depth (PPD), clinical attachment loss (CAL), plaque index (PLI), and sulcular bleeding index (SBI), while the secondary outcomes were tooth mobility (TM), glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), total effective rate, and adverse effects. Results . Eleven randomized controlled trials (RCT) were included in the meta-analysis. The pooled results showed PPD (WMD = 1.07, 95%CI: (0.82, 1.33), P < 0.00001, I 2 = 89%), CAL (WMD = 0.78, 95%CI: (0.62, 0.93), P < 0.00001, I 2 = 58%), PLI (WMD = 0.44, 95%CI: (0.09, 0.79), P = 0.01, I 2 = 97%), SBI (WMD = 0.87, 95%CI: (0.79, 0.95), P < 0.00001, I 2 = 37%), TM (WMD = 0.26, 95%CI: (0.21, 0.30), P < 0.00001, I 2 = 31%), HbA1c (WMD = 0.48, 95%CI: (0.28, 0.67), P < 0.00001, I 2 = 26%), FBG (WMD = 1.34, 95%CI: (0.96, 1.72), P < 0.00001, I 2 = 52%), total effective rate (RR = 1.24, 95%CI: (1.14, 1.34), P < 0.00001, I 2 = 0%), and adverse effects (RR = 0.78, 95%CI: (0.20, 3.03), P = 0.72, I 2 = 0%) in the traditional Chinese medicine based on the method of "nourishing kidney and clearing heat" + routine western medicine treatment (periodontal basic treatment, PBT, with or without antibiotic) group were significantly improved compared to control group, but no significant difference was observed for PLI at 2–3 months and 6 months. Conclusions . This review supports traditional Chinese medicine based on the method of "nourishing kidney and clearing heat" as an adjuvant to routine western medicine treatment in the management of diabetes mellitus patients with periodontitis. Within the limits of the evidence, the well-designed, long-term efficacy, and high-quality multicenter RCTs need to be further confirmed.